2021
DOI: 10.1108/ijilt-07-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

Intention to continue using mobile learning: the effects of perceived values and role of locus of control

Abstract: PurposeThe study aims to determine the factor of perceived machine learning adoption (MLA) values that affect learners' intention to continue using (ICU), the extent of their relationships in the learners' ICU and the role of locus of control (LOC) in their relationship.Design/methodology/approachThe study employed a rigorous literature review of MLA studies that lead to a multidimensional value-based theoretical model. This model combined the theory of consumption and altruistic values. Simple descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
2
8
0
1
Order By: Relevance
“…To the best knowledge of the researchers, investigations of the perceived valueengagement association are non-existent, but studies in the online learning context that are similar to some extent (El-Haddadeh et al, 2019;Hajli, 2015) can help explain these unique results. The most comparable study was by Magsayo (2021) who found similar results regarding the FUV-AE, SOV-AE (only for Malaysian students in this study) and SPV-AE (only for male students in this study) associations. The Thai students might derive more acceptance and prestige (social value aspects) from face-to-face learning and that, in turn, enhances their engagement while the opposite is true for Malaysian students.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…To the best knowledge of the researchers, investigations of the perceived valueengagement association are non-existent, but studies in the online learning context that are similar to some extent (El-Haddadeh et al, 2019;Hajli, 2015) can help explain these unique results. The most comparable study was by Magsayo (2021) who found similar results regarding the FUV-AE, SOV-AE (only for Malaysian students in this study) and SPV-AE (only for male students in this study) associations. The Thai students might derive more acceptance and prestige (social value aspects) from face-to-face learning and that, in turn, enhances their engagement while the opposite is true for Malaysian students.…”
Section: Discussionsupporting
confidence: 81%
“…Perceived value. This measure consisted of 30 items adapted from Magsayo (2021) with slight altering of phrases from mobile learning to online learning context. The six dimensions of perceived value had five items each and had internal consistency values of 0.918 (functional value, FUV), 0.900 (social value, SOV), 0.903 (epistemic value, EPV), 0.882 (conditional value, COV), 0.897 (ethical value, ETV), 0.862 (spiritual value, SPV).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Todo lo anterior configura un escenario donde surgen nuevas necesidades, exigencias e intereses a causa de la COVID-19 como la sincronía ubicua, la distancia social, los protocolos de bioseguridad y la multired social (Sophonhiranrak, 2021); también el empleo del móvil para casi todas las actividades comunicativas en tiempo de pandemia (el llamado boom de las apps) (Romero-Rodríguez et al, 2021a); así también el incremento y mayor evidencialidad de la brecha digital por falta de conectividad y otros recursos (Mella-Norambuena et al, 2021;Loayza-Maturrano, 2021). Asimismo, surge la necesidad de una nueva enseñanza virtual (pizarras digitales virtuales, videotutoriales, repositorios virtuales); un distinto aprendizaje no presencial (aulas virtuales, aprendizaje sincrónica y asincrónico) (Magsayo, 2021); así como aprendizaje móvil mediado por redes sociales: el whatsapp for learning, el telegram for learning y los webinar for learning López-Moranchel, et al (2021); Sophea et al (2022);Valverde-Macias & Llerena Izquierdo (2022).…”
Section: Introductionunclassified